Analisis Unsur-unsur Sastra dalam Surah Al Lahab - Aimaniar, Ummi Robihah; Khasanah, Uswatun; Ridwan, Nur Anisa (Prosiding Konferensi Nasional Bahasa Arab, 2023)
This research aims to explain and analyze the elements of Arabic literature contained in Surah Al-Lahab from the Al-Quran. In this research, researchers used descriptive qualitative research methods to describe and interpret the elements of Arabic literature contained in this surah. The analysis in this research includes an analysis of elements of Arabic literature such as feelings and emotions, imagination, ideas, and the form of the literary work. The results of this research reveal that there are several feelings and emotions, the majority of which in all verses discuss God's anger and hatred towards Abu Lahab and his wife. Then the imagination (al-khayyal) contained in Surah al-Lahab is neatly arranged, and there are no plot defects, so the depiction is clear and feels real. Likewise with al-fikrah and as-shurah, where the two are interconnected. The dominant ideas in this surah contain warnings, condemnations, and punishments for the actions of Abu Lahab and Umm Jamil, who opposed the Prophet Muhammad and the teachings of Islam. This research can provide a deeper understanding of the elements of Arabic literature in the Al-Quran and the messages contained in this surah.